2016
DOI: 10.1371/journal.pone.0147236
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Long Non-Coding RNA HOTAIR Correlates with Disease Progression in Bladder Cancer and Is Contained in Bladder Cancer Patient Urinary Exosomes

Abstract: Exosomes are 30-150nM membrane-bound secreted vesicles that are readily isolated from biological fluids such as urine (UEs). Exosomes contain proteins, micro RNA (miRNA), messenger RNA (mRNA), and long non-coding RNA (lncRNA) from their cells of origin. Although miRNA, protein and lncRNA have been isolated from serum as potential biomarkers for benign and malignant disease, it is unknown if lncRNAs in UEs from urothelial bladder cancer (UBC) patients can serve as biomarkers. lncRNAs are > 200 nucleotide long t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
200
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(203 citation statements)
references
References 86 publications
(94 reference statements)
1
200
0
2
Order By: Relevance
“…The value of circulating lncRNA in predicting cancer is an intensely researched topic (28), but just a few papers assess if the lncRNAs are traveling via exosomes. There are three advantages in using exosomal lncRNAs as biomarkers: (I) lncRNAs inside the exosome are protected from RNases and can be presumed that the integrity and function of the lncRNAs are not altered (29); (II) the quantity of exosomal lncRNAs is high compared to other types of EVs (30); and (III) the expression of many lncRNAs is tissue specific (31). Therefore, profiling the exosomal lncRNAs can lead to the development of valuable diagnostic markers.…”
Section: Exosome Lncrnas As Potential Cancer Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of circulating lncRNA in predicting cancer is an intensely researched topic (28), but just a few papers assess if the lncRNAs are traveling via exosomes. There are three advantages in using exosomal lncRNAs as biomarkers: (I) lncRNAs inside the exosome are protected from RNases and can be presumed that the integrity and function of the lncRNAs are not altered (29); (II) the quantity of exosomal lncRNAs is high compared to other types of EVs (30); and (III) the expression of many lncRNAs is tissue specific (31). Therefore, profiling the exosomal lncRNAs can lead to the development of valuable diagnostic markers.…”
Section: Exosome Lncrnas As Potential Cancer Biomarkersmentioning
confidence: 99%
“…The in vitro knock-down of HOTAIR leads to a decrease in migration, a less invasive phenotype and reduced epithelial to mesenchymal transition (EMT) factors expression. The same research group reported seven more lncRNAs that are overexpressed in urine exosomes of invasive UBC patients: HOXA cluster antisense RNA 2 (HOX-AS-2), MALAT-1, Long intergenic non-protein coding RNA regulator of reprogramming (LINC-ROR), Hydatidiform mole associated and imprinted non-protein coding RNA 1 (HYMA1), Long intergenic non-protein coding RNA 477 (LINC00477), LOC 100506688, and Orthodenticle homeobox 2 antisense RNA 1 (OTX2-AS1) (29). The lncRNA, Prostate cancer antigen 3 (PCA3), is an already FDA approved urine biomarker for prostate adenocarcinoma.…”
Section: Exosome Lncrnas As Potential Cancer Biomarkersmentioning
confidence: 99%
“…It has been experimentally validated that lncRNAs are involved in the etiology and pathogenesis of various cancers, including BLCA [13][14][15][16][17][18][19][20]. The recent advances in high-throughput data technologies, including RNAsequencing and microarrays, has guided the identification of lncRNAs for prospective clinical application in BLCA [12,[21][22][23]. However, most previous studies focused on the clinical value of individual lncRNAs, which has limited potential for future clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomal lincRNA and miRNA are also detected in the urine of prostate and bladder cancer patients [77][78][79]. Bryzgunova et al [77] reported that the level of miR-19b, normalized to that of miR-16, in urine-derived exosomes was significantly lower in prostate cancer patients than in healthy donors .…”
Section: Diagnosismentioning
confidence: 99%